A method for preparing high temperature resistant hafnium boride ceramic material

By preparing composite hafnium boronide powder and composite silicon carbide powder and adopting hot press sintering technology, the shortcomings of traditional high-temperature resistant ceramic materials in thermal stability, thermal shock resistance, mechanical and thermal conductivity are solved, and high-density and excellent performance high-temperature hafnium boronide ceramic materials are achieved.

CN119143507BActive Publication Date: 2025-03-25SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411604099.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-25
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Traditional high-temperature resistant ceramic materials are difficult to meet the comprehensive requirements of thermal stability, thermal shock resistance, mechanical properties, and thermal conductivity, especially the high melting point of hafnium boride, which leads to difficulty in sintering and densification.

Method used

The preparation method of composite hafnium boride powder and composite silicon carbide powder is adopted to form a porous composite through the preparation and firing process of primary, secondary and tertiary coated powder, which increases the binding force between hafnium boride and silicon carbide, and improves the density of the material through hot pressing and sintering technology.

Benefits of technology

The prepared high-temperature resistant hafnium boronide ceramic materials have high density, significantly improved thermal stability, thermal shock resistance, mechanical properties, and thermal conductivity, and can maintain excellent physical properties at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a preparation method of a high temperature resistant hafnium boride ceramic material, belonging to the technical field of ceramic materials, the preparation method is composed of the following steps: preparing composite hafnium boride powder, preparing composite silicon carbide powder, mixing, sintering; the preparation of composite hafnium boride powder is composed of the following steps: preparing a primary coated powder, preparing a secondary coated powder, preparing a tertiary coated powder, firing; the preparation of composite silicon carbide powder is composed of the following steps: primary treatment, secondary treatment; the mixing, after the composite hafnium boride powder, composite silicon carbide powder, and anhydrous ethanol are mixed according to a mass ratio of 70-72:28-30:160-200, ball milling 4-5h and then drying to obtain a mixed powder. The high temperature resistant hafnium boride ceramic material prepared by the present invention has high density, good thermal stability, thermal shock resistance, mechanical properties, and thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a method for preparing a high-temperature resistant hafnium boride ceramic material. Background Art

[0002] High temperature resistant ceramic material is a kind of ceramic material with good heat resistance, excellent thermal stability and thermal shock resistance. It can maintain its original physical properties at high temperature. It also has excellent mechanical properties, thermal conductivity and chemical stability. It is widely used in electronics, chemical industry, aerospace and other fields.

[0003] Currently, commonly used high-temperature resistant ceramic materials include alumina ceramic materials, boron nitride ceramic materials, and silicon carbide ceramic materials. With the advancement of science and the development of industry, the demand for high-temperature resistant ceramics is gradually increasing, and the requirements are becoming higher and higher. Traditional high-temperature resistant ceramic materials are difficult to meet the comprehensive requirements for thermal stability, thermal shock resistance, mechanical properties, and thermal conductivity.

[0004] Hafnium boride is a gray crystal with a metallic luster. It has a high melting point of 3250°C and excellent thermal conductivity. When hafnium boride is used in the preparation of high-temperature resistant ceramic materials, high-temperature resistant hafnium boride ceramic materials with excellent comprehensive performance can be obtained. However, hafnium boride has a high melting point and is difficult to sinter and densify, resulting in an excessively high sintering temperature, which further affects the density, mechanical properties, and thermal conductivity of the high-temperature resistant ceramics.

[0005] There are two most commonly used solutions to the above problems. The first solution is to directly mix hafnium boride with other high-temperature resistant ceramics and sintering aids and then perform hot pressing sintering to prepare composite high-temperature resistant ceramics. However, the dispersibility of hafnium boride is poor, resulting in uneven mixing between hafnium boride and other high-temperature resistant ceramics and sintering aids. In addition, the bonding strength between hafnium boride and other high-temperature resistant ceramics is poor, which further affects the thermal stability, thermal shock resistance and mechanical properties of the prepared composite high-temperature resistant ceramics. The second solution is to use hafnium oxide and boron source to prepare the composite high-temperature resistant ceramics. , and carbon source are used as raw materials to prepare hafnium boride micropowder with high purity and small particle size, and then the hafnium boride micropowder is evenly mixed with other high-temperature resistant ceramics and sintering aids and then hot-pressed and sintered to prepare composite high-temperature resistant ceramics. However, in the preparation of hafnium boride micropowder by carbon thermal reduction method, the hafnium boride micropowder is easy to aggregate and grow, resulting in uneven particle size distribution of the prepared hafnium boride micropowder, and there is still the problem of poor bonding between hafnium boride and other high-temperature resistant ceramics, which further affects the thermal stability, thermal shock resistance and mechanical properties of the prepared composite high-temperature resistant ceramics. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a high-temperature resistant hafnium boride ceramic material. The prepared high-temperature resistant hafnium boride ceramic material has high density, good thermal stability, thermal shock resistance, mechanical properties and thermal conductivity.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a high temperature resistant hafnium boride ceramic material, comprising the following steps: preparing composite hafnium boride powder, preparing composite silicon carbide powder, mixing, and sintering;

[0009] The preparation of the composite hafnium boride powder comprises the following steps: preparing a primary coated powder, preparing a secondary coated powder, preparing a tertiary coated powder, and sintering;

[0010] The first-level coated powder is prepared by mixing hafnium oxide powder, hexadecyltrimethylammonium bromide and the first portion of water, stirring at a stirring speed of 300-500 rpm for 50-60 minutes at room temperature, filtering, taking the filter residue and drying, mixing with the block polyether F127 and the second portion of water, stirring at a stirring speed of 300-500 rpm for 90-100 minutes at room temperature, filtering, taking the filter residue and drying to obtain the first-level coated powder;

[0011] In the preparation of the primary coated powder, the mass ratio of hafnium oxide powder, hexadecyltrimethylammonium bromide, the first portion of water, block polyether F127, and the second portion of water is 18-20:42-45:6500-7000:200-210:9000-9500;

[0012] The particle size of the hafnium oxide powder is 5 μm;

[0013] The preparation of the secondary coated powder comprises mixing boron carbide powder, boron oxide powder, activated carbon powder, hexadecyltrimethylammonium bromide and the first portion of water, stirring at a stirring speed of 300-500 rpm for 70-80 minutes at room temperature, centrifuging, taking the precipitate and drying it, mixing it with the primary coated powder and the second portion of water, stirring at a stirring speed of 300-500 rpm for 140-150 minutes at room temperature, filtering, taking the filter residue and drying it to obtain the secondary coated powder;

[0014] In the preparation of the secondary coated powder, the mass ratio of boron carbide powder, boron oxide powder, activated carbon powder, hexadecyltrimethylammonium bromide, the first portion of water, and the second portion of water is 4-5:2.1-2.2:12-13:23-25:3500-4000:4000-4200;

[0015] The mass ratio of the boron carbide powder in the preparation of the secondary coated powder to the hafnium oxide powder in the preparation of the primary coated powder is 4-5:18-20;

[0016] The particle size of the boron carbide powder is 50 nm;

[0017] The particle size of the boron oxide powder is 50 nm;

[0018] The particle size of the activated carbon powder is 50 nm;

[0019] The preparation of the third-level coated powder comprises mixing alkaline silica sol and water, stirring at a stirring speed of 100-200 rpm for 20-30 minutes at room temperature, adding the second-level coated powder, stirring at a stirring speed of 300-500 rpm for 140-150 minutes at room temperature, filtering, taking the filter residue and drying it to obtain hafnium boride micropowder;

[0020] In the preparation of the three-level coated powder, the mass ratio of alkaline silica sol to water is 120-130:3000-3500;

[0021] The mass ratio of the alkaline silica sol in preparing the third-level coated powder to the boron carbide powder in preparing the second-level coated powder is 120-130:4-5;

[0022] The alkaline silica sol has a pH of 9, a silica mass content of 30%, and a particle size of 20 nm;

[0023] The sintering comprises heating the hafnium boride powder to 1550-1600°C at a heating rate of 10-15°C / min in an argon atmosphere, keeping the temperature at 1550-1600°C for 80-90min, cooling naturally to room temperature, and then heating the powder to 450-500°C at a heating rate of 10-15°C / min in an oxygen atmosphere, keeping the temperature at 450-500°C for 7-8h, and cooling naturally to room temperature to obtain composite hafnium boride powder;

[0024] The preparation of composite silicon carbide powder comprises the following steps: primary treatment, secondary treatment;

[0025] The primary treatment comprises mixing large-particle silicon carbide powder, hexadecyltrimethylammonium bromide and water, stirring at room temperature at a stirring speed of 300-500 rpm for 50-60 minutes, filtering, taking the filter residue and drying it to obtain primary treated silicon carbide powder;

[0026] In the primary treatment, the mass ratio of large-particle silicon carbide powder, hexadecyltrimethylammonium bromide, and water is 200-210:40-45:7500-8000;

[0027] The particle size of the large-particle silicon carbide powder is 5 μm;

[0028] The secondary treatment comprises mixing small-particle silicon carbide, alumina powder, aluminum powder, sodium dodecylbenzene sulfonate and the first portion of water, stirring at a stirring speed of 300-500 rpm for 80-100 min at room temperature, centrifuging, taking the precipitate and drying it, mixing it with the primary-treated silicon carbide powder and the second portion of water, stirring at a stirring speed of 300-500 rpm for 160-180 min at room temperature, filtering, taking the filter residue and drying it to obtain composite silicon carbide powder;

[0029] In the secondary treatment, the mass ratio of small-size silicon carbide, alumina powder, aluminum powder, sodium dodecylbenzene sulfonate, the first portion of water, and the second portion of water is 30-32:14-16:12-13:42-45:7500-8000:6000-7000;

[0030] The mass ratio of the small-particle silicon carbide in the secondary treatment to the large-particle silicon carbide powder in the primary treatment is 30-32:200-210;

[0031] The particle size of the small-particle silicon carbide powder is 50 nm;

[0032] The particle size of the aluminum oxide powder is 50 nm;

[0033] The particle size of the aluminum powder is 50 nm;

[0034] The mixing material comprises mixing composite hafnium boride powder, composite silicon carbide powder and anhydrous ethanol in a mass ratio of 70-72:28-30:160-200, ball milling for 4-5 hours and then drying to obtain a mixed powder;

[0035] The sintering comprises adding the mixed powder into a mold, and hot pressing and sintering for 80-90 minutes at a temperature of 1900-2000° C. and a pressure of 27-30 MPa to obtain a high temperature resistant hafnium boride ceramic material.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The preparation method of the high temperature resistant hafnium boride ceramic material of the present invention comprises preparing composite hafnium boride powder and composite silicon carbide powder respectively, and then mixing the composite hafnium boride powder and composite silicon carbide powder and sintering them. The preparation method of composite hafnium boride powder comprises preparing primary coated powder, preparing secondary coated powder, preparing tertiary coated powder and sintering, wherein the preparation of primary coated powder comprises surface modification of hafnium oxide powder with hexadecyltrimethylammonium bromide, and then coating the block polyether F127 by self-assembly method to obtain primary coated powder; the preparation of secondary coated powder comprises surface modification of boron carbide powder, boron oxide powder and activated carbon powder with hexadecyltrimethylammonium bromide, and then combining the powder with the surface of primary coated powder by self-assembly method to obtain secondary coated powder. Powder; the preparation of the third-level coated powder is to coat the second-level coated powder with alkaline silica sol, and the adsorption of the alkaline silica sol is used to bind to the surface of the second-level coated powder to obtain the third-level coated powder; the firing is to heat-treat the third-level coated powder. During the heat treatment, a carbon thermal reduction reaction occurs between hafnium oxide, boron carbide, boron oxide, and activated carbon to generate hafnium boride. The activated carbon also reacts with the silicon dioxide in the alkaline silica sol to generate silicon carbide, and then the excess carbon is removed to obtain a porous composite of hafnium boride and silicon carbide, that is, composite hafnium boride powder. The alkaline silica sol limits the aggregation and growth of hafnium boride micropowder, avoiding the uneven particle size distribution of the prepared hafnium boride micropowder; the block copolymer forms porous carbon after carbonization, which, while serving as a carbon source, can also increase the reaction contact area and promote the formation of hafnium boride and silicon carbide; the composite of hafnium boride and silicon carbide can also improve the binding force between hafnium boride and silicon carbide. The preparation method of composite silicon carbide powder comprises a primary treatment and a secondary treatment, wherein the primary treatment is to use hexadecyltrimethylammonium bromide to perform surface treatment on large-particle silicon carbide powder to obtain primary-treated silicon carbide powder; the secondary treatment is to use sodium dodecylbenzene sulfonate to perform surface treatment on small-particle silicon carbide, alumina powder and aluminum powder, and then to coat the surface of the primary-treated silicon carbide powder by a self-assembly method to obtain composite silicon carbide powder; when the composite silicon carbide powder and the composite hafnium boride powder are mixed and mixed, the sodium dodecylbenzene sulfonate on the surface of the composite silicon carbide powder can promote dispersion; when hot pressing sintering is performed, the alumina and aluminum on the surface of the composite silicon carbide powder serve as sintering aids to promote sintering densification; the silicon carbide on the surface of the composite silicon carbide powder can promote grain growth and promote the combination of the composite silicon carbide powder and the composite hafnium boride powder;

[0038] (2) The method for preparing the high temperature resistant hafnium boride ceramic material of the present invention has a high density. The density of the high temperature resistant hafnium boride ceramic material prepared by the present invention can reach 99.1-99.3%;

[0039] (3) The method for preparing the high temperature resistant hafnium boride ceramic material of the present invention has good mechanical properties. The high temperature resistant hafnium boride ceramic material prepared by the present invention has a flexural strength of 632.5-647.8 MPa at room temperature and a fracture toughness of 9.04-9.18 MPa·m at room temperature. 1 / 2 , the Vickers hardness at room temperature can reach 13.87-14.22GPa;

[0040] (4) The method for preparing the high temperature resistant hafnium boride ceramic material of the present invention has good thermal conductivity. The thermal conductivity of the high temperature resistant hafnium boride ceramic material prepared by the present invention can reach 128-132 W / (m·K) at room temperature;

[0041] (5) The method for preparing the high temperature resistant hafnium boride ceramic material of the present invention has good thermal stability. The flexural strength of the high temperature resistant hafnium boride ceramic material prepared by the present invention can reach 610.2-617.6 MPa at 1800°C;

[0042] (6) The method for preparing the high-temperature resistant hafnium boride ceramic material of the present invention has good thermal shock resistance. The high-temperature resistant hafnium boride ceramic material prepared by the present invention is heated to 1500°C for 4 hours, kept at 1500°C for 10 minutes, and then cooled to 20°C by cold air. This is regarded as one cycle. After 20 cycles in total, there is no crack on the surface. DETAILED DESCRIPTION

[0043] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0044] Example 1

[0045] A method for preparing a high temperature resistant hafnium boride ceramic material, specifically comprising:

[0046] 1. Preparation of composite hafnium boride powder:

[0047] (1) Preparation of primary coated powder: 18 g of hafnium oxide powder, 42 g of hexadecyltrimethylammonium bromide and 6500 g of water were mixed, stirred at room temperature at a stirring speed of 300 rpm for 50 min, filtered, the filter residue was taken and dried, and then mixed with 200 g of block polyether F127 and 9000 g of water, stirred at room temperature at a stirring speed of 300 rpm for 90 min, filtered, the filter residue was taken and dried to obtain a primary coated powder;

[0048] The particle size of the hafnium oxide powder is 5 μm;

[0049] (2) Preparation of secondary coated powder: 4 g of boron carbide powder, 2.1 g of boron oxide powder, 12 g of activated carbon powder, 23 g of hexadecyltrimethylammonium bromide and 3500 g of water were mixed, stirred at 300 rpm for 70 min at room temperature, centrifuged, the precipitate was taken and dried, and then mixed with all the primary coated powder obtained in the preparation of the primary coated powder in step (1) and 4000 g of water, stirred at 300 rpm for 140 min at room temperature, filtered, and the filter residue was taken and dried to obtain a secondary coated powder;

[0050] The particle size of the boron carbide powder is 50 nm;

[0051] The particle size of the boron oxide powder is 50 nm;

[0052] The particle size of the activated carbon powder is 50 nm;

[0053] (3) Preparation of tertiary coated powder: 120 g of alkaline silica sol and 3000 g of water were mixed, and the mixture was stirred at 100 rpm for 20 min at room temperature. All the secondary coated powder obtained in step (2) for preparing the secondary coated powder was added, and the mixture was stirred at 300 rpm for 140 min at room temperature. The mixture was filtered, and the residue was collected and dried to obtain hafnium boride micropowder.

[0054] The alkaline silica sol has a pH of 9, a silica mass content of 30%, and a particle size of 20 nm;

[0055] (4) Firing: In an argon atmosphere, the hafnium boride powder is heated to 1550°C at a heating rate of 10°C / min, kept at 1550°C for 80 min, and naturally cooled to room temperature. Then, in an oxygen atmosphere, the temperature is increased to 450°C at a heating rate of 10°C / min, kept at 450°C for 7 h, and naturally cooled to room temperature to obtain a composite hafnium boride powder.

[0056] 2. Preparation of composite silicon carbide powder:

[0057] (1) Primary treatment: 200 g of large-particle silicon carbide powder, 40 g of hexadecyltrimethylammonium bromide, and 7500 g of water were mixed, stirred at room temperature at a stirring speed of 300 rpm for 50 min, filtered, and the filter residue was taken and dried to obtain primary treated silicon carbide powder;

[0058] The particle size of the large-particle silicon carbide powder is 5 μm;

[0059] (2) Secondary treatment: 30 g of small-particle silicon carbide, 14 g of alumina powder, 12 g of aluminum powder, 42 g of sodium dodecylbenzene sulfonate, and 7500 g of water were mixed, stirred at 300 rpm for 80 min at room temperature, centrifuged, the precipitate was taken and dried, and then mixed with all the primary-treated silicon carbide powder obtained in the primary treatment in step (1) and 6000 g of water, stirred at 300 rpm for 160 min at room temperature, filtered, and the filter residue was taken and dried to obtain composite silicon carbide powder;

[0060] The particle size of the small-particle silicon carbide powder is 50 nm;

[0061] The particle size of the aluminum oxide powder is 50 nm;

[0062] The particle size of the aluminum powder is 50 nm;

[0063] 3. Mixing: Mix the composite hafnium boride powder, composite silicon carbide powder and anhydrous ethanol in a mass ratio of 70:28:160, ball mill for 4 hours and then dry to obtain a mixed powder;

[0064] 4. Sintering: Add the mixed powder into a mold and hot press sinter for 80 minutes at a temperature of 1900°C and a pressure of 27 MPa to obtain a high temperature resistant hafnium boride ceramic material.

[0065] Example 2

[0066] A method for preparing a high temperature resistant hafnium boride ceramic material, specifically comprising:

[0067] 1. Preparation of composite hafnium boride powder:

[0068] (1) Preparation of primary coated powder: 19 g of hafnium oxide powder, 44 g of hexadecyltrimethylammonium bromide and 6800 g of water were mixed, stirred at room temperature at a stirring speed of 400 rpm for 55 min, filtered, the filter residue was taken and dried, and then mixed with 205 g of block polyether F127 and 9200 g of water, stirred at room temperature at a stirring speed of 400 rpm for 95 min, filtered, the filter residue was taken and dried to obtain a primary coated powder;

[0069] The particle size of the hafnium oxide powder is 5 μm;

[0070] (2) Preparation of secondary coated powder: 4.5 g of boron carbide powder, 2.1 g of boron oxide powder, 12.5 g of activated carbon powder, 24 g of hexadecyltrimethylammonium bromide and 3800 g of water were mixed, stirred at 400 rpm for 75 min at room temperature, centrifuged, the precipitate was taken and dried, and then mixed with all the primary coated powder obtained in the preparation of the primary coated powder in step (1) and 4100 g of water, stirred at 400 rpm for 145 min at room temperature, filtered, and the filtrate was taken and dried to obtain a secondary coated powder;

[0071] The particle size of the boron carbide powder is 50 nm;

[0072] The particle size of the boron oxide powder is 50 nm;

[0073] The particle size of the activated carbon powder is 50 nm;

[0074] (3) Preparation of tertiary coated powder: 125 g of alkaline silica sol and 3300 g of water were mixed, and the mixture was stirred at 150 rpm for 25 min at room temperature. All the secondary coated powder obtained in step (2) for preparing the secondary coated powder was added, and the mixture was stirred at 400 rpm for 145 min at room temperature. The mixture was filtered, and the residue was collected and dried to obtain hafnium boride micropowder.

[0075] The alkaline silica sol has a pH of 9, a silica mass content of 30%, and a particle size of 20 nm;

[0076] (4) Firing: In an argon atmosphere, the hafnium boride powder is heated to 1580°C at a heating rate of 12°C / min, kept at 1580°C for 85 min, and naturally cooled to room temperature. Then, in an oxygen atmosphere, the temperature is increased to 480°C at a heating rate of 12°C / min, kept at 480°C for 7.5 h, and naturally cooled to room temperature to obtain a composite hafnium boride powder.

[0077] 2. Preparation of composite silicon carbide powder:

[0078] (1) Primary treatment: 205 g of large-particle silicon carbide powder, 42 g of hexadecyltrimethylammonium bromide, and 7800 g of water were mixed, stirred at room temperature at a stirring speed of 400 rpm for 55 min, filtered, and the filter residue was taken and dried to obtain primary treated silicon carbide powder;

[0079] The particle size of the large-particle silicon carbide powder is 5 μm;

[0080] (2) Secondary treatment: 31 g of small-particle silicon carbide, 15 g of alumina powder, 12.5 g of aluminum powder, 44 g of sodium dodecylbenzene sulfonate, and 7800 g of water were mixed, stirred at 400 rpm for 90 min at room temperature, centrifuged, the precipitate was taken and dried, and then mixed with all the primary-treated silicon carbide powder obtained in the primary treatment in step (1) and 6500 g of water, stirred at 400 rpm for 170 min at room temperature, filtered, and the filter residue was taken and dried to obtain composite silicon carbide powder;

[0081] The particle size of the small-particle silicon carbide powder is 50 nm;

[0082] The particle size of the aluminum oxide powder is 50 nm;

[0083] The particle size of the aluminum powder is 50 nm;

[0084] 3. Mixing: Mix the composite hafnium boride powder, composite silicon carbide powder and anhydrous ethanol in a mass ratio of 71:29:180, ball mill for 4.5 hours and then dry to obtain a mixed powder;

[0085] 4. Sintering: Add the mixed powder into a mold and hot press sinter for 85 minutes at a temperature of 1950°C and a pressure of 28 MPa to obtain a high temperature resistant hafnium boride ceramic material.

[0086] Example 3

[0087] A method for preparing a high temperature resistant hafnium boride ceramic material, specifically comprising:

[0088] 1. Preparation of composite hafnium boride powder:

[0089] (1) Preparation of primary coated powder: 20 g of hafnium oxide powder, 45 g of hexadecyltrimethylammonium bromide and 7000 g of water were mixed, stirred at room temperature at a stirring speed of 500 rpm for 60 min, filtered, the filter residue was taken and dried, and then mixed with 210 g of block polyether F127 and 9500 g of water, stirred at room temperature at a stirring speed of 500 rpm for 100 min, filtered, the filter residue was taken and dried to obtain primary coated powder;

[0090] The particle size of the hafnium oxide powder is 5 μm;

[0091] (2) Preparation of secondary coated powder: 5 g of boron carbide powder, 2.2 g of boron oxide powder, 13 g of activated carbon powder, 25 g of hexadecyltrimethylammonium bromide and 4000 g of water were mixed, stirred at 500 rpm for 80 min at room temperature, centrifuged, the precipitate was taken and dried, and then mixed with all the primary coated powder obtained in the preparation of the primary coated powder in step (1) and 4200 g of water, stirred at 500 rpm for 150 min at room temperature, filtered, and the filter residue was taken and dried to obtain a secondary coated powder;

[0092] The particle size of the boron carbide powder is 50 nm;

[0093] The particle size of the boron oxide powder is 50 nm;

[0094] The particle size of the activated carbon powder is 50 nm;

[0095] (3) Preparation of tertiary coated powder: 130 g of alkaline silica sol and 3500 g of water were mixed, and the mixture was stirred at 200 rpm for 30 min at room temperature. All the secondary coated powder obtained in step (2) for preparing the secondary coated powder was added, and the mixture was stirred at 500 rpm for 150 min at room temperature. The mixture was filtered, and the residue was collected and dried to obtain hafnium boride micropowder.

[0096] The alkaline silica sol has a pH of 9, a silica mass content of 30%, and a particle size of 20 nm;

[0097] (4) Firing: In an argon atmosphere, the hafnium boride powder is heated to 1600°C at a heating rate of 15°C / min, kept at 1600°C for 90 minutes, and naturally cooled to room temperature. Then, in an oxygen atmosphere, the temperature is increased to 500°C at a heating rate of 15°C / min, kept at 500°C for 8 hours, and naturally cooled to room temperature to obtain a composite hafnium boride powder.

[0098] 2. Preparation of composite silicon carbide powder:

[0099] (1) Primary treatment: 210 g of large-particle silicon carbide powder, 45 g of hexadecyltrimethylammonium bromide, and 8000 g of water were mixed, stirred at room temperature at a stirring speed of 500 rpm for 60 min, filtered, and the filter residue was taken and dried to obtain primary treated silicon carbide powder;

[0100] The particle size of the large-particle silicon carbide powder is 5 μm;

[0101] (2) Secondary treatment: 32 g of small-particle silicon carbide, 16 g of alumina powder, 13 g of aluminum powder, 45 g of sodium dodecylbenzene sulfonate, and 8000 g of water were mixed, stirred at a stirring speed of 500 rpm for 100 min at room temperature, centrifuged, the precipitate was taken and dried, and then mixed with all the primary-treated silicon carbide powder obtained in the primary treatment in step (1) and 7000 g of water, stirred at a stirring speed of 500 rpm for 180 min at room temperature, filtered, and the filter residue was taken and dried to obtain composite silicon carbide powder;

[0102] The particle size of the small-particle silicon carbide powder is 50 nm;

[0103] The particle size of the aluminum oxide powder is 50 nm;

[0104] The particle size of the aluminum powder is 50 nm;

[0105] 3. Mixing: Mix the composite hafnium boride powder, composite silicon carbide powder and anhydrous ethanol in a mass ratio of 72:30:200, ball mill for 5 hours and then dry to obtain a mixed powder;

[0106] 4. Sintering: Add the mixed powder into a mold and hot press sinter for 90 minutes at a temperature of 2000°C and a pressure of 30 MPa to obtain a high temperature resistant hafnium boride ceramic material.

[0107] Comparative Example 1

[0108] Based on the preparation method of Example 2, the first step of preparing the composite hafnium boride powder is omitted, and the first step of preparing the composite hafnium boride powder is changed to:

[0109] 4.5 g of boron carbide powder, 2.1 g of boron oxide powder, 12.5 g of activated carbon powder, and 3800 g of water were mixed, stirred at a stirring speed of 400 rpm for 75 min at room temperature, centrifuged, the precipitate was taken and dried, mixed with 19 g of hafnium oxide powder and 4100 g of water, and stirred at a stirring speed of 400 rpm for 145 min at room temperature to obtain composite hafnium boride powder;

[0110] The particle size of the boron carbide powder is 50 nm;

[0111] The particle size of the boron oxide powder is 50 nm;

[0112] The particle size of the activated carbon powder is 50 nm.

[0113] The other operations are the same as those in Example 2.

[0114] Comparative Example 2

[0115] On the basis of the preparation method of Example 2, the second step of preparing the composite silicon carbide powder is omitted, and in the third mixing step, an equal mass of silicon carbide powder with a particle size of 5 μm is used instead of the composite silicon carbide powder.

[0116] The other operations are the same as those in Example 2.

[0117] Performance Test 1

[0118] The density, room temperature flexural strength, room temperature fracture toughness, room temperature Vickers hardness, room temperature thermal conductivity, and 1800° C. flexural strength of the high temperature resistant hafnium boride ceramic materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested, and the test results are as follows:

[0119]

[0120] Performance Test 2

[0121] The thermal shock resistance of the high temperature resistant hafnium boride ceramic materials prepared in Examples 1-3 and Comparative Examples 1-2 was tested. Specifically, the high temperature resistant hafnium boride ceramic materials were heated to 1500°C for 4 hours, kept at 1500°C for 10 minutes, and then cooled to 20°C by cold air. This was regarded as one cycle. A total of 20 cycles were performed to observe whether there were cracks on the surface of the high temperature resistant hafnium boride ceramic materials. The observation results are as follows:

[0122]

[0123] It can be seen from the above results that the density of the high temperature resistant hafnium boride ceramic materials prepared in Comparative Examples 1-2 is lower than that of the high temperature resistant hafnium boride ceramic materials prepared in Examples 1-3, and the thermal stability, thermal shock resistance, mechanical properties and thermal conductivity of the high temperature resistant hafnium boride ceramic materials prepared in Comparative Examples 1-2 are worse than those of the high temperature resistant hafnium boride ceramic materials prepared in Examples 1-3.

[0124] Unless otherwise specified, all percentages used in the present invention are by mass.

[0125] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high temperature resistant hafnium boride ceramic material, characterized in that: The method comprises the following steps: preparing composite hafnium boride powder, preparing composite silicon carbide powder, mixing materials, and sintering; The preparation of the composite hafnium boride powder comprises the following steps: preparing a primary coated powder, preparing a secondary coated powder, preparing a tertiary coated powder, and sintering; The first-level coated powder is prepared by mixing hafnium oxide powder, hexadecyltrimethylammonium bromide, and the first portion of water, stirring at room temperature, filtering, taking the filter residue and drying, and mixing with block polyether F127 and the second portion of water, stirring at room temperature, filtering, taking the filter residue and drying to obtain the first-level coated powder; To prepare the secondary coated powder, boron carbide powder, boron oxide powder, activated carbon powder, hexadecyltrimethylammonium bromide and the first portion of water are mixed, stirred at room temperature, centrifuged, the precipitate is taken and dried, and then mixed with the primary coated powder and the second portion of water, stirred at room temperature, filtered, and the filter residue is taken and dried to obtain the secondary coated powder; The preparation of the third-level coated powder comprises mixing alkaline silica sol and water, stirring at room temperature, adding the second-level coated powder, stirring at room temperature, filtering, taking the filter residue and drying it to obtain hafnium boride micropowder; The sintering comprises heating the hafnium boride powder to 1550-1600°C at a heating rate of 10-15°C / min in an argon atmosphere, keeping the temperature at 1550-1600°C for 80-90min, cooling naturally to room temperature, and then heating the powder to 450-500°C at a heating rate of 10-15°C / min in an oxygen atmosphere, keeping the temperature at 450-500°C for 7-8h, and cooling naturally to room temperature to obtain composite hafnium boride powder; The preparation of composite silicon carbide powder comprises the following steps: primary treatment, secondary treatment; The primary treatment comprises mixing large-particle silicon carbide powder, hexadecyltrimethylammonium bromide and water, stirring at room temperature, filtering, taking the filter residue and drying it to obtain the primary treated silicon carbide powder; The secondary treatment comprises mixing small-particle silicon carbide, alumina powder, aluminum powder, sodium dodecylbenzene sulfonate and the first portion of water, stirring at room temperature, centrifuging, taking the precipitate and drying it, mixing it with the primary-treated silicon carbide powder and the second portion of water, stirring at room temperature, filtering, taking the filter residue and drying it to obtain composite silicon carbide powder; The mixing material comprises mixing composite hafnium boride powder, composite silicon carbide powder and anhydrous ethanol in a mass ratio of 70-72:28-30:160-200, ball milling for 4-5 hours and drying to obtain a mixed powder.

2. The method for preparing the high temperature resistant hafnium boride ceramic material according to claim 1, characterized in that: In the preparation of the primary coated powder, the mass ratio of hafnium oxide powder, hexadecyltrimethylammonium bromide, the first portion of water, block polyether F127, and the second portion of water is 18-20:42-45:6500-7000:200-210:9000-9500; The particle size of the hafnium oxide powder is 5 μm.

3. The method for preparing the high temperature resistant hafnium boride ceramic material according to claim 1, characterized in that: In the preparation of the secondary coated powder, the mass ratio of boron carbide powder, boron oxide powder, activated carbon powder, hexadecyltrimethylammonium bromide, the first portion of water, and the second portion of water is 4-5:2.1-2.2:12-13:23-25:3500-4000:4000-4200; The mass ratio of the boron carbide powder in the preparation of the secondary coated powder to the hafnium oxide powder in the preparation of the primary coated powder is 4-5:18-20; The particle size of the boron carbide powder is 50 nm; The particle size of the boron oxide powder is 50 nm; The particle size of the activated carbon powder is 50 nm.

4. The method for preparing the high temperature resistant hafnium boride ceramic material according to claim 1, characterized in that: In the preparation of the three-level coated powder, the mass ratio of alkaline silica sol to water is 120-130:3000-3500; The mass ratio of the alkaline silica sol in preparing the third-level coated powder to the boron carbide powder in preparing the second-level coated powder is 120-130:4-5; The alkaline silica sol has a pH of 9, a silicon dioxide mass content of 30%, and a particle size of 20 nm.

5. The method for preparing the high temperature resistant hafnium boride ceramic material according to claim 1, characterized in that: In the primary treatment, the mass ratio of large-particle silicon carbide powder, hexadecyltrimethylammonium bromide, and water is 200-210:40-45:7500-8000; The particle size of the large-particle silicon carbide powder is 5 μm.

6. The method for preparing the high temperature resistant hafnium boride ceramic material according to claim 1, characterized in that: In the secondary treatment, the mass ratio of small-size silicon carbide, alumina powder, aluminum powder, sodium dodecylbenzene sulfonate, the first portion of water, and the second portion of water is 30-32:14-16:12-13:42-45:7500-8000:6000-7000; The mass ratio of the small-particle silicon carbide in the secondary treatment to the large-particle silicon carbide powder in the primary treatment is 30-32:200-210; The particle size of the small-particle silicon carbide powder is 50 nm; The particle size of the aluminum oxide powder is 50 nm; The particle size of the aluminum powder is 50 nm.

7. The method for preparing the high temperature resistant hafnium boride ceramic material according to claim 1, characterized in that: The sintering comprises adding the mixed powder into a mold, and hot pressing and sintering for 80-90 minutes at a temperature of 1900-2000° C. and a pressure of 27-30 MPa to obtain a high temperature resistant hafnium boride ceramic material.

Citation Information

Patent Citations

  • Method for preparing hafnium boride powder

    CN102249687A

  • Hafnium boride-silicon carbide-graphite-tantalum silicide composite ceramic heating body and preparation method thereof

    CN106083063A